Annandale, Dumfriesshire und Galloway, Großbritannien. Forschungen entlang einer Römischen Straße. Die Arbeiten des Jahres 2017 - Beusing, Ruth (e-Forschungsberichte des DAI, 2018)
The tabular eminence of Burnswark Hill in Dumfriesshire has intrigued settlers at least from the Bronze Age onwards, its surrounding landscape in the Scottish Lowlands is a distinguished livestock farming region. Positioned in intervisibility with the Hadrian’s Wall, the area also raised Roman interest in the late Iron Age and was brought under Roman control very early. The project studies evidences of the local and the Roman population along a stretch of the Roman Road between the Roman Forts of Birrens and Ladyward. Thus, it seeks to understand the spatial and consequent social interactions between locals and within the showcase area.